Testing to no avail? the diagnostic and treatment conundrum in patients with extraesophageal manifestations of gastroesophageal reflux disease - Naik, Rishi D.; Patel, Dhyanesh A.; Vaezi, Michael F. (Annals of Laparoscopic and Endoscopic Surgery; Vol 2 (September 2017): Annals of Laparoscopic and Endoscopic Surgery, 2017)
Extraesophageal reflux (EER), which includes cough, asthma, and laryngopharyngeal reflux (LPR), is an important and prevalent disease state with a large economic burden of up to fifty billion dollars, largely due to the pharmaceutical costs of empiric treatment (1).